Ways to implement the tasks of moral and aesthetic education in teaching fine arts - Stukalenko Нина; Tarasenko Юлия; Dmitrieva Олеся (Рroblems of engineering and professional education, 2023)
In this article, the authors study the moral aesthetic problem, and show the main ways of its implementation in the study of visual arts.